2018
DOI: 10.1038/s41426-018-0097-y
|View full text |Cite
|
Sign up to set email alerts
|

The concordance between upper and lower respiratory microbiota in children with Mycoplasma pneumoniae pneumonia

Abstract: In recent years, the morbidity of Mycoplasma pneumoniae pneumonia (MPP) has dramatically increased in China. An increasing number of studies indicate that an imbalance in the respiratory microbiota is associated with respiratory infection. We selected 28 hospitalized patients infected with M. pneumoniae and 32 healthy children. Nasopharyngeal (NP) and oropharyngeal (OP) swabs were collected from healthy children, whereas NP, OP and bronchoalveolar lavage (BAL) specimens were collected from patients. Microbiota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 31 publications
1
37
1
Order By: Relevance
“…Microbial balance in the specific tissue was associated with the development of disease [27]. Increasing studies have demonstrated that microbial diversity in the BLAF was significantly decreased and relationship with the disease severity in patients with pneumonia such as bacterial pneumonia, Mycoplasma pneumoniae pneumonia [28,29]. In the BLAF of patients with Spn-induced pneumonia, Spn were accumulated and had low microbial diversity because Spn secreted the abundant various virulence factors to inhibit the other bacterial survival [30].…”
Section: Discussionmentioning
confidence: 99%
“…Microbial balance in the specific tissue was associated with the development of disease [27]. Increasing studies have demonstrated that microbial diversity in the BLAF was significantly decreased and relationship with the disease severity in patients with pneumonia such as bacterial pneumonia, Mycoplasma pneumoniae pneumonia [28,29]. In the BLAF of patients with Spn-induced pneumonia, Spn were accumulated and had low microbial diversity because Spn secreted the abundant various virulence factors to inhibit the other bacterial survival [30].…”
Section: Discussionmentioning
confidence: 99%
“…Increasingly, reports demonstrate that specific dominant bacteria are associated with severe acute respiratory infections [6, 15, 46], but there have been no meaningful correlations identified between disease severity and M. pneumonia —or indeed between the other species of reassembled bacteria found in the OP microbiota of children with MPP. In our previous studies, we confirmed the succession of M. pneumoniae infection in NP to OP and lung, and determined an association between M. pneumoniae load in the lung microbiota with disease severity [14].…”
Section: Discussionmentioning
confidence: 66%
“…Morbidity and mortality related to MPP is increasing in Chinese children. The development of RM studies has improved our understanding of the microbial aetiology of MPP by revealing infection-associated RM imbalances [13, 14]. However, microbial functions and host–microbiota interactions in the RM of patients with MPP remain to be explored, particularly for novel microbial species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mycoplasma pneumoniae is a common respiratory pathogen that is responsible for the community-acquired pneumonia (CAP), especially in children. [13] Furthermore, it also triggers the exacerbation of asthmatic symptoms and wheezes in children. [49] It has been reported that M pneumoniae accounts for 7% to 40% of all CAP in children 3 to 15 years of age.…”
Section: Introductionmentioning
confidence: 99%